2014
DOI: 10.1186/1477-7819-12-56
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the clinical outcomes of patients with invasive lobular carcinoma and invasive ductal carcinoma of the breast according to molecular subtype in a Korean population

Abstract: BackgroundTo investigate the clinicopathological characteristics and the survival outcomes of invasive lobular carcinoma (ILC) patients compared to invasive ductal carcinoma (IDC) patients according to their molecular subtype.MethodsWe compared the clinicopathological characteristics, breast cancer-specific survival (BCSS) and overall survival (OS) between patients with IDC (n = 14,547) and ILC (n = 528).ResultsThe ILC presented with a larger tumor size, more advanced cancer stage, increased rate of hormonal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Compared with IDCs, ILCs were more likely to be positive for ER and PR and less likely to overexpress HER2 and Ki-67. The results of the present study are consistent with previous studies [ 12 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Compared with IDCs, ILCs were more likely to be positive for ER and PR and less likely to overexpress HER2 and Ki-67. The results of the present study are consistent with previous studies [ 12 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…These studies have primarily included invasive ductal carcinoma (IDC), which comprises 72% to 80% of all invasive breast cancers [ 11 ]. Invasive lobular carcinoma (ILC) is the second most common breast cancer after IDC and accounts for 5% to 15% of all breast cancers [ 11 , 12 ], but there is a lack of data associating the SUVmax and prognostic factors in ILC in the existing literature. ILCs have exhibited low FDG uptake in previous studies [ 3 , 4 , 7 - 9 , 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the previous literature, we found that relative to ductal cancers, lobular cancers were less frequent among black versus white women [36–39], less frequent among younger women [22, 3638, 4043], but more common among premenopausal women after controlling for age [2325]. As has been shown previously, we observed that 88% of lobular tumors in our study were Luminal A subtype, which closely matches previous studies of lobular tumors (~80–90%, [7, 8, 11, 15, 17, 44, 45]), and is considerably higher than the overall prevalence of Luminal A subtype among invasive breast cancers (50%, [6, 7]). We also found that ductal tumors displayed diversity in clinical subtype and contained a majority of the TN and HER2+ tumor types, as others have reported [717].…”
Section: Discussionsupporting
confidence: 90%
“…ILC, which is also known as infiltrating lobular carcinoma, is the second-most-common histological type of breast cancer, and its incidence is increasing. [ 13 ] Although ILC is less common than invasive ductal breast cancer (IDC), the proportion of cases with ILC is gradually increasing. [ 14 , 15 ] ILC tumors have a better long-term outlook and tend to be less aggressive than IDC tumors, but they are inclined to metastasize to the genital tracts, the gastrointestinal system, and meninges, and additional more commonly transfer to atypical sites.…”
Section: Discussionmentioning
confidence: 99%